Harnessing Transcription Factors as Potential Tools to Enhance Grain Size Under Stressful Abiotic Conditions in Cereal Crops - Watt, Calum; Zhou, Gaofeng; Li, Chengdao (Frontiers in Plant Science, 2020)
Predicted climate change is widely cited to significantly reduce yields of the major cereal crop species in a period where demand is rapidly rising due to a growing global population. This requires exhaustive research to develop genetic resources in order to address the expected production deficiencies which will largely been driven by abiotic stress. Modification of multiple genes is an approach that can address the predicted challenges however it is time consuming and costly to modify multiple genes simultaneously. Transcription factors represent a group of proteins regulating multiple genes simultaneously and are therefore promising targets to concurrently improve multiple traits concurrently, such as abiotic stress tolerance and grain size (a contributor to yield). Many studies have identified the complex role that transcription factors of multiple families have contributed toward abiotic stress tolerance or grain size, although research addressing both simultaneously is in its infancy despite its potential significance for cereal crop improvement. Here we discuss the potential role that transcription factors may contribute toward improving cereal crop productivity under adverse environmental conditions and offer research objectives that need to be addressed before the modification of transcription factors becomes routinely used to positively manipulate multiple target traits.